INFLUENCE OF BARIUM SALT ON OPTICAL BEHAVIOR OF PVA BASED SOLID POLYMER ELECTROLYTES - Abdullah, Omed Gh. (European Scientific Journal, ESJ, 2014)
Solid polymer electrolyte films based on polyvinyl alcohol complexed with Barium nitrate salt at different weight percent were prepared using solution cast technique. The optical absorption coefficient was used to study the nature of electronic transitions between the valence and conduction bands. From the derivation of Tauc’s relation it was found that the optical absorption is due to direct- and indirect allowed transitions. The reduction of energy band gap and increase of tail localized states was observed with increasing Barium nitrate content. The values of refractive index, extinction coefficient, the optical complex dielectric constant have been also calculated. The higher refractive index of solid polymer electrolytes was attributed to the higher molecular packing density compared to that of pure polymer. The increase of optical dielectric constant with increasing salt concentration indicates the presence of a higher density of states and increase in the amount of charge carrier concentration within the polymer electrolyte films.